Kajian Penerapan Standar Operasional Prosedur Pembuatan dan Penyajian Pasta Aglio e Olio di Hotel Lido - Rosita, Risma; Rahardjo, Sekti (Universitas Ahmad Dahlan, 2025)
This research is based on guest complaints that the author found from hotel guest comments and social media on the aglio e olio pasta dish at the Lido Lake Resort by MNC hotel. The complaint shows guest dissatisfaction with the aglio e olio pasta dish. The purpose of this study was to examine the implementation of the SOP (Standard Operating Procedure) for making and serving aglio e olio pasta. Explaining the factors of obstacles faced in implementing the standard operating procedure for making and serving aglio e olio pasta in the hot kitchen. In a standard operating procedure, the standard recipe is usually included as part of the kitchen operation to ensure that all kitchen staff follow the same standard recipe and produce consistent products. This research was conducted using qualitative methods with observation, interview and documentation data collection techniques. The results of the study concluded that the study of the SOP for making and serving aglio e olio pasta at the commis in the hot kitchen of the Lido hotel was not fully implemented properly. Four constraints were found in implementing the SOP for making and serving aglio e olio pasta. From the results of this study, it is expected that there will be implementation of supervision or control to ensure that every kitchen staff complies with the SOP in addition to the implementation of a continuous training program.